Bilingual Curriculum in EFL Speaking: Teachers' Strategies at Islamic Boarding School: English - Silmi Kaffah; Wahed Hasim; Anne Ratna Suminar (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2026)
English proficiency is one of the most important skills in education, leading many schools to implement a bilingual curriculum to improve students' English language skills, particularly their speaking ability. Although the implementation of the bilingual curriculum continues to develop, understanding of the strategies teachers use to apply it in English as a Foreign Language (EFL) Speaking classes, particularly in Islamic boarding school settings, remains limited. This study aims to explore teachers' strategies in implementing a bilingual curriculum in EFL Speaking classes. This study employed a qualitative approach with a case study design involving three English teachers at an Islamic boarding school in Garut Regency, West Java. Research data were collected through semi-structured interviews and non-participant observation. The data were then analyzed using the interactive analysis model proposed by Miles et al. (2014), which includes data condensation, data display, and conclusion drawing and verification. The results showed that teachers applied three main strategies in implementing the bilingual curriculum, namely learning strategies, motivational strategies, and classroom management strategies. These three strategies were used to build students' confidence in speaking English and to create a supportive bilingual learning environment. These findings provide a more comprehensive understanding of teachers' strategies in implementing a bilingual curriculum in EFL Speaking instruction within an Islamic boarding school setting.